Analysis of thermal coal pricing and the coal price distortion in China from the perspective of market forces. (July 2017) - Cui, Herui; Wei, Pengbang
Abstract: The price of thermal coal has always been the focus of the debate between coal mining industry and electric power industry. The thermal coal price is always lower than other same quality coal, and this phenomenon of thermal coal price distortion has been existing in China for a long time. The distortion coal price can not reflect the external cost and the resource scarcity of coal, which could result in environment deteriorating and inefficient resource allocation. This paper studied the phenomenon of thermal coal price distortion through economic theoretical modeling and empirical cointegration analysis from the perspective of market forces. The results show that thermal coal price is determined by electricity price, the prediction elasticity of a electricity enterprise, price elasticity of demand of electricity, the input prediction elasticity of a electricity enterprise and the price elasticity of supply of thermal coal. The main reason of coal price distortion is the unbalance market force of coal industry and thermal coal generation industry. The distortion rate of coal price is positively related to the market force of electric power industry and negatively related to the industrial concentration of coal industry. Highlights: This paper studied thermal coal pricing and the coal price distortion in China. The main reason of coal price distortion is the unbalance market force. Thermal coal price is also influenced by electricity price and price elasticity of demand of electricity. The distortion rate of coal price is negatively related to the industrial concentration of coal industry.